Socio-demographic and behavioural profile of women in polygamous relationships in South Africa: a retrospective analysis of the 2002 population-based household survey data - Musawenkosi L. H. Mabaso; Nthabiseng F. Malope; Leickness C. Simbayi (BMC, 2018)
Abstract Background The prevalence and effect of polygamous relationships may have serious reproductive and /or health consequences for women. In South Africa, unlike in other sub-Saharan countries, no nationwide survey has investigated polygamy except for the 2002 HIV/AIDS population-based household survey. The aim of this study was to profile socio-demographic and behavioural characteristics associated with women in polygamous relationships in South Africa using the 2002 survey data. Methods The survey data were collected using a multi-stage stratified cluster randomised sampling design. Bivariate and multivariate logistic regression models were used to assess the relationship between polygamy, and selected socio-demographic and behavioural factors. Results Of 1437 women who responded to the question on polygamy, 8.3% reported being in a polygamous marriage. Women in polygamous marriages were significantly less likely to have tertiary education [OR = 0.03(95% CI: 0.00-0.28), p = 0.003], to have money for food and clothes [OR = 0.12 (95% CI: 0.06-0.27), p < 0.001], to have a sexual partner five years younger [OR = 0.10 (95% CI: 0.01-0.94), p = 0.044] or sexual partner within 5 years older or younger [OR = 0.35 (95% CI: 0.13-0.991), p = 0.032]. They were also significantly more likely to have two or more sexual partners [OR = 20.42 (95% CI: 1.10-379.89), p = 0.043]. Conclusion The finding that polygamy is associated with uneducated and women of low economic means, who have relationships with older men and multiple sexual partners warrants further attention. Contemporary studies on polygamy are needed in South Africa.